PENGARUH LATIHAN MENGGIRING BOLA KE BIDANG AMAN TERHADAP KETERAMPILAN MENGGIRING BOLA PADA SSB CHEVRON - Ardiansyah Ardiansyah; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstark: The problem in this research was that during the interview with the coach said that athletes really needed to be trained in dribbling speed because the obtained pre-pre test showed that most dribbling speed was in the poor category, the aim of this research was to improve of the athlete. The form of this research is (one group pretest-postest design) with the population of the Chevron SSB team. The sample in this research was the entire population, a total of 15 people. The tool used in this research was the dribble test, which aims to determine the effect of dribbling training to a safe area. Based on the analysis of the normality test on the independent variable (X), it produces a LoMax of 0.132 and an L table of 0.220. while the dependent variable (Y) returns a LoMax of 0.161 and an L table of 0.220. This means that LoMax <L The data table is normally distributed. When testing the hypothesis for the t-distribution, it can be concluded that between the variable x and the variable y the value of t = 6.833 is obtained, then tcount> ttable, namely (6.833)> (1.761), then Ha is accepted in other words, there is an effect of dribbling training to the safe field on the dribbling ability ball on SSB Chevron.Key Words: Dribble practice to a safe field, Dribbling skills